2008
DOI: 10.1177/1044207308314948
|View full text |Cite
|
Sign up to set email alerts
|

Disability Harassment Observed by Teachers in Special Education

Abstract: The occurrence and impact of disability harassment of students in special education apparently have a low priority for official policy makers and education administrators. Literature on policies of generic school bullying, one state's prohibition of pupil harassment, and a federal memorandum of school-based disability harassment are reviewed. The purpose of this preliminary study is to investigate observed occurrences of harassment of students with disabilities based on 15 specific types of harassment conduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
1
19
0
2
Order By: Relevance
“…In all of the cases reported by student teachers in this study, the bullying took the form of nasty comments or jibes or the social exclusion of the children with SEN from classroom group work or playground games. The study therefore concurs with Holzbauer () who found that the use of slurs, epithets, mockery and ostracism were more common than theft or physical aggression in cases of disability harassment. Moreover, although there were many instances recounted by student teachers of children being very kind and helpful towards their peers with physical disabilities, this was often a helper–helpee asymmetrical friendship rather than a truly equal relationship (Frederickson, ; Meyer et al., ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In all of the cases reported by student teachers in this study, the bullying took the form of nasty comments or jibes or the social exclusion of the children with SEN from classroom group work or playground games. The study therefore concurs with Holzbauer () who found that the use of slurs, epithets, mockery and ostracism were more common than theft or physical aggression in cases of disability harassment. Moreover, although there were many instances recounted by student teachers of children being very kind and helpful towards their peers with physical disabilities, this was often a helper–helpee asymmetrical friendship rather than a truly equal relationship (Frederickson, ; Meyer et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…However, students had not been taught anything at all about how to help prevent or deal effectively with bullying incidents involving children with SEN in particular, irrespective of their role (perpetrator, target, bystander, etc.). Given the consistent research findings (Thompson, Whitney and Smith, 1994;Mishna, 2003;Mencap, 2007;Holzbauer, 2008;Department of Education Northern Ireland, 2011), which suggest that children with SEN are more likely to be victims of bullying than other children, the argument is persuasive that ITE courses should address this important issue affecting the most vulnerable children in our schools. In this study, students expressed a desire for this content to be introduced but for the input to be practical, solution focused and delivered in collaboration with experienced, practising teachers from schools.…”
Section: Discussionmentioning
confidence: 98%
“…Since Dawkins (1996) introduced the subject of childhood bullying in the professional literature, more attention has been given to this difficult problem. The victimization of children with various disabilities is now well-documented (Williams, 2007;Holzbauer, 2008;Lindsay, Dockrell, & Mackie, 2008). In addition, the long-term consequences of bullying, which include psychiatric disorders, anxiety disorders, aggressive behavior, and impaired self-worth, are beginning to be recognized (Sourander et al, 2007;Piek et al, 2005).…”
Section: Downloaded By [Chulalongkorn University] At 21:24 02 Januarymentioning
confidence: 98%
“…Αξίζει να σημειωθεί πως οι μαθητές με νοητικά ελλείμματα πολλές φορές δεν είναι σε θέση να αναγνωρίσουν το εκφοβισμό που βιώνουν ή, ακόμα και αν τον αναγνωρίσουν, ίσως να μην μπορούν να τον καταγγείλουν (Holzbauer, 2008). Όταν οι μαθητές καταφέρουν να καταγγείλουν τέτοια περιστατικά, συνήθως αναχαιτίζονται επειδήπρώτον, θεωρούν πως μια καταγγελία δεν θα γίνει πιστευτή από τους άλλουςκαι δεύτερον, θεωρούν πως δεν θα γίνουν κινήσεις για την βελτίωση της κατάστασης και, τέλος φοβούνται για αντίποινα, σε περίπτωση που γίνει γνωστή η καταγγελία.…”
Section: ποσοστά και παράγοντες θυματοποίησηςunclassified
“…Ακολούθησαν σε συχνότητα η γελοιοποίηση και η μίμηση. Ανεξαρτήτως της συχνότητας των παρατηρήσεων ακόμα και οι πιο ακραίες μορφές εκφοβισμού είχαν παρατηρηθεί έστω από κάποιους εκπαιδευτικούς (Holzbauer, 2008).…”
Section: ποσοστά και παράγοντες θυματοποίησηςunclassified